Brushstrokes towards a democratization of virtual teaching (Revista Electrónica REDINE, 2020)
In a Post-industrial society, characterized by an economic foundation stemming from the dynamism of the market, where the generation of income is its premise, the democratization of thought is necessary, which will lead to the organization of man as a thinking being, generator of new ideas and executor of actions, to be catapulted into an intellectual evolution; It is then that we are in the presence of a Knowledge Society proper. Hence, this essay seeks to expose the nuances that would lead to new professions such as Virtual Teaching to the contribution of these new knowledge that every society requires, it is from this that, it starts from the ideological and political characteristics of post-industrial society, which They have given way to new forms of work, they have seen in Information and Communication Technologies (ICT) an important alloy for their execution, in this way the so-called Telework and Virtual Teaching are presented as part of these new disciplines.
Keywords: Democracy; Virtual Teaching; Knowledge Society; Postindustrial; Telecommuting